2019
DOI: 10.1371/journal.pone.0212332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of the SurePure Turbulator ultraviolet-C irradiation equipment on inactivation of different enveloped and non-enveloped viruses inoculated in commercially collected liquid animal plasma

Abstract: The objective of this study was to evaluate the effectiveness of the SurePure Turbulator ultraviolet-C (UV-C, 254 nm wavelength) irradiation equipment on inactivation of different enveloped and non-enveloped viruses in commercially collected liquid animal plasma. Specifically, Pseudorabies virus (PRV), Porcine reproductive and respiratory syndrome virus (PRRSV), Porcine epidemic diarrhea virus (PEDV), Bovine viral diarrhea virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 56 publications
4
41
2
1
Order By: Relevance
“…The World Health Organization (WHO) (WHO, 2004) guidelines on viral inactivation and removal procedures intended to assure the viral safety of human blood plasma products establishes that a robust inactivation process should be capable of removing or inactivating at least 4 logs of a wide range of viruses (WHO, 2004). In previous studies, the UV-C irradiation of liquid plasma was able to inactive 4 logs of different bacteria and viruses (Polo et al, 2015;Blázquez et al, 2017Blázquez et al, , 2019 and the present study also demonstrated the lack of transmission of any virus after being UV irradiated at a minimum of 3000 J/L. Therefore, UV-C irradiation complies with the WHO definition of a robust inactivation process.…”
Section: Discussionsupporting
confidence: 83%
“…The World Health Organization (WHO) (WHO, 2004) guidelines on viral inactivation and removal procedures intended to assure the viral safety of human blood plasma products establishes that a robust inactivation process should be capable of removing or inactivating at least 4 logs of a wide range of viruses (WHO, 2004). In previous studies, the UV-C irradiation of liquid plasma was able to inactive 4 logs of different bacteria and viruses (Polo et al, 2015;Blázquez et al, 2017Blázquez et al, , 2019 and the present study also demonstrated the lack of transmission of any virus after being UV irradiated at a minimum of 3000 J/L. Therefore, UV-C irradiation complies with the WHO definition of a robust inactivation process.…”
Section: Discussionsupporting
confidence: 83%
“…To validate the effectiveness of the plasma UV-C irradiation measured by means of the viral load reduction in cell culture, a bioassay was done with different groups of pigs injected intraperitoneally with UV-C irradiated commercial liquid plasma at 0 J/L (untreated plasma), 3000 J/L, and at 9000 J/L [77]. The results of the bioassay showed that none of the pigs in the groups that received liquid plasma irradiated by UV-C at either dose became infected or seroconverted against the different virus genomes that were detected in the initial plasma (PCV-2, PRRSV (European strains), SIV, PPV, HEV, Rotavirus A (RVA); thus, confirming the efficacy of UV-C demonstrated in vitro in a previous study [74]. Detection of a viral genome in the untreated liquid plasma does not imply infectivity by a given virus.…”
Section: Uv Irradiation Effect On Bacteria Survival In Sdpsupporting
confidence: 85%
“…The effect of UV-C on different viruses of interest in the swine industry was also determined [74]. Viruses selected for testing was based on their different physicochemical characteristics, types of genome (DNA or RNA), genome lengths (long and short genomes), presence or absence of envelope and resistance to other inactivation processes.…”
Section: Uv Irradiation Effect On Bacteria Survival In Sdpmentioning
confidence: 99%
“…We instead applied multiple categorical predictors. With inactivation of viruses in blood products without describing how attenuation was considered in their reported doses (10,(56)(57)(58). Although these doses are likely representative for these fluids, they cannot be extrapolated to other matrices.…”
Section: Numerous Uv254 Rate Constants Are Available But Only For a mentioning
confidence: 99%